GDNF revisited: A novel mammalian cell-derived variant form of GDNF increases dopamine turnover and improves brain biodistribution. (15th March 2019) - Grondin, Richard; Littrell, O. Meagan; Zhang, Zhiming; Ai, Yi; Huettl, Peter; Pomerleau, Francois; Quintero, Jorge E.; Andersen, Anders H.; Stenslik, Mallory J.; Bradley, Luke H.; Lemmon, Jack; O'Neill, Michael J.; et al.
Abstract: Parkinson's disease (PD) is a disorder affecting dopamine neurons for which there is no cure. Glial cell line-derived neurotrophic factor (GDNF) and the closely related protein neurturin are two trophic factors with demonstrated neuroprotective and neurorestorative properties on dopamine neurons in multiple animal species. However, GDNF and neurturin Phase-2 clinical trials have failed to demonstrate a significant level of improvement over placebo controls. Insufficient drug distribution in the brain parenchyma has been proposed as a major contributing factor for the lack of clinical efficacy in the Phase-2 trial patients. To address this issue, a novel mammalian cell-derived variant form of GDNF (GDNFv) was designed to promote better tissue distribution by reducing its heparin binding to the extracellular matrix and key amino acids were substituted to enhance its chemical stability. Administration of this fully glycosylated GDNFv in the normal rat striatum increased dopamine turnover and produced significantly greater brain distribution than E. coli -produced wildtype GDNF (GDNFwt). Intrastriatal GDNFv also protected midbrain dopamine neuron function in 6-hydroxydopamine-lesioned rats. Studies conducted in normal adult rhesus macaques support that GDNFv was well tolerated in all animals and demonstrated a greater volume of distribution than GDNFwt in the brain following intrastriatal infusion. Importantly, favorable physiological activity of potential therapeutic value was maintained in this variant trophic factor with significant target activation in GDNFv recipients as indicated by dopamine turnover modulation. These data suggest that GDNFv may be a promising drug candidate for the treatment of PD. Additional studies are needed in non-human primates with dopamine depletion. This article is part of the Special Issue entitled 'Drug Repurposing: old molecules, new ways to fast track drug discovery and development for CNS disorders'. Highlights: Neurotrophic factors have great therapeutic potential for Parkinson's disease. Insufficient brain distribution has limited the clinical use of trophic factors. A variant form of GDNF shows increased dopamine turnover and brain bioavailability. GDNF variant is well tolerated in treated animals. GDNF variant represents a promising drug candidate for treating parkinsonian patients.